Modelagem de distribuição presente, passada e futura de cactos Mandacaru da Diagonal Seca da América do Sul - Oliveira, João Victor Mendonça de (Universidade Federal de São Carlos, 2021)
The influence of paleoclimates on current population dynamics and geographic distribution of living organisms is widely recognized, as well as the influence of anthropogenic activities on future climate. Closely related species, with a wide spatial distribution and associated with different biomes, have great value for biogeographic and ecological studies, such as the case of the species that belong to the genus Cereus Mill. The genus belongs to the Cactaceae family (Caryophyllales order) and is divided into four subgenera, including its namesake Cereus, which has four main evolutionary lineages, including Clade A1, which includes seven species of Cereus. In the present work, a survey of occurrence records of Clade A1 species was carried out to infer projections of geographic distribution in the present, past and future, using data on climatic variables (temperature, precipitation and soil) available in open databases as input to perform Species Distribution Modelling (SDM), using MaxEnt software. The results of the paleomodelling carried out for five of the seven species of the genus, due to the insufficient number of points recovered for the two remaining ones, showed a great influence of the climatic events of the Quaternary in their distribution. Other possible factors, such as soil composition for Cereus hexagonus and Cereus jamacaru, Tertiary tectonic pulses for Cereus hildmannianus, and physical barriers (river and mountain range) for Cereus stenogonus, may also have influenced the species distribution. Future models for Cereus bicolor, C. hexagonus, C. jamacaru and C. stenogonus showed expansion in the distribution of the species, which are inserted in dry biomes or intense dry periods, while for C. hildmannianus, which is inserted in the humid biome of the Atlantic Forest, a retraction in its distribution was detected, which may suggest future processes of aridification in the Atlantic Forest, Amazon and Pantanal regions. Such results may suggest the expansion of aridification and desertification processes in the Atlantic Forest, Amazon, Pantanal and Caatinga biomes. Thus, it is concluded that abiotic variables of climate and soil of the Quaternary had a strong influence on the distribution of Clade A1 species. In addition, the study showed that anthropic activities could alter the future distribution of the dry and wet biomes of South America, and it contributes to conservation actions and decision-making by conservation area managers.
Modelling the current, past and future distribution of Mandacaru cactus in the South American Dry Diagonal
Keywords: Biogeografia; Paleomodelagem; Biogeography; Paleomodelling; CIENCIAS BIOLOGICAS::BOTANICA::FITOGEOGRAFIA